2020
DOI: 10.1108/et-01-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Project-based learning (PBL): outcomes of students’ engagement in an external consultancy project in Oman

Abstract: PurposeProject-Based Learning (PBL) is an innovative approach to learning that employs a multitude of strategies critical for success in the twenty-first century. It exposes students to the real world, opens an extended inquiry process, and boosts their communication skills and interdisciplinary learning. However, the extant literature on PBL places more emphasis on learning through internal rather than external projects. Industrial collaboration projects build partnerships and provide opportunities to work on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 99 publications
(148 reference statements)
1
17
1
7
Order By: Relevance
“…This might be because of not having much experience on projects work, or because of problems with the division of labor. Unlike these findings, majority of students in Belwal et al's (2020) study asserted effective time management as the most important contribution of project work. Regarding time management, a difference between Belwal et al's study and this one is that the time allocated for the project was quite limited and there were tasks that needed to be completed hourly as participants mentioned.…”
Section: Findings and Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This might be because of not having much experience on projects work, or because of problems with the division of labor. Unlike these findings, majority of students in Belwal et al's (2020) study asserted effective time management as the most important contribution of project work. Regarding time management, a difference between Belwal et al's study and this one is that the time allocated for the project was quite limited and there were tasks that needed to be completed hourly as participants mentioned.…”
Section: Findings and Discussioncontrasting
confidence: 56%
“…Similarly, Chen and Yang's (2019) meta-analysis of the effects of the PjBL method on academic achievement compared to traditional methods revealed that the method had an average to higher positive effect on academic achievement. According to findings of similar studies, project-based learning contributes to higher levels of perception and learning by creating an effective classroom environment and ensures high student achievement and performance (Belwal et al, 2020;Cifci, 2015;Çelik et al, 2018;Hugerat, 2016). Participants in another study stated that to the research findings PjBL method increases active participation, makes the lesson comprehensible, efficient, instructive, motivating, and makes learning permanent (Şahin et al, 2020).…”
Section: Statementsmentioning
confidence: 99%
“…From the works of several authors in the learning process, pupils independently find the problem, and independently solve the problem and check its correctness, evaluate it as the highest activity in the project method (Belwal, Belwal, Sufian, & Al Badi, 2020;Perez-Sanchez & Lopez-Jimenez, 2020;Chanpet, Chomsuwan, & Murphy, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the Omani educational context, there are very few studies that investigated the application of PBL in higher education institutions (Belwal et al, 2020;Dauletova, 2014) and as far as the researchers are aware, there have been no studies investigating the use of PBL in teacher-preparation programs. This study fills this gap.…”
Section: Studies Examining Pbl In Learning/teaching In Higher Educationmentioning
confidence: 99%